Assessment of policy conflict using systems thinking: A case study of carbon footprint reduction on Irish dairy farms. Issue 101 (November 2019) - Paterson, Kirsty C.; Holden, Nicholas M.
Highlights: Causal loop diagrams revealed policy conflict. Systems thinking provided scientific policy evaluation. Improving eco-efficiency on farm can increase absolute impact of the sector. Abstract: The dairy sector in Ireland is in potential conflict with environmental regulations due to the abolition of European Union dairy quotas and domestic agricultural expansion policy. The 'Dairy Carbon Navigator' aims to help Irish farmers reduce the carbon footprint of their milk and enhance economic viability by suggesting actions that could be taken to reduce carbon footprint. The tool is a national solution to Ireland's contribution to the global problem of climate change and food production. It was designed to drive a decrease in net global greenhouse gas (GHG) emissions per unit milk produced but may conflict with legislation and policy designed to reduce total national emissions. The aim of this work was to assess the feasibility of taking a systems thinking approach to identify areas of policy conflict, using carbon footprint reduction on Irish dairy farms as a case study. This was done by developing a causal loop diagram (CLD), which reflected a typical Irish dairy farm. The causal loop diagram was used to show the direction of change in farm level impact caused by implementing the Dairy Carbon Navigator recommendations. This was used to identify potential conflicts between farm management changes and the achievement of the EU Effort Sharing Decision (regulating GHG emissions), National Emissions Ceiling Directive (regulating some GHG emissions and acidification) and the Water Framework and Nitrates Directives (regulating eutrophication). It was found that extending the grazing season would increase absolute greenhouse gas emissions and absolute eutrophication but decrease carbon footprint. Increasing total herd intake per unit milk would also increase absolute impact. However, across all recommendations, reductions in carbon footprint, acidification and eutrophication per unit milk solids was predicted, due to increased efficiency. These results reflected the rising emissions detailed in the most recent national inventory report and reported decline in water quality, threatening the current overall good status of Irish waterbodies. The qualitative methods used to develop the CLD may introduce bias, but this was moderated by using workshops with interested parties. However, the main benefit of the approach was the identification of the differences between improving production efficiency (impact per unit output) and absolute mitigation of environmental impacts (decrease in national inventory). Systems thinking facilitates an interdisciplinary approach to policy evaluation from initiation to implementation, and highlights issues that may be overlooked when policy instruments are focused on a single factor.